Structural Racism in Healthcare: Nurses' Ethical and Professional Responsibility to Lead Structural Reform - Chanchal Kurup; Deepa Rijal (Nursing Open, 2026)
ABSTRACT Background Structural racism remains a pervasive and deeply embedded determinant of healthcare inequity globally. Despite strengthened professional standards and policy commitments to equity, racialised populations continue to experience substantial disparities in healthcare access, quality, safety and outcomes. These inequities are sustained not only through interpersonal encounters but also through structural conditions embedded within healthcare systems, workforce arrangements, governance processes and organisational cultures. Structural racism additionally affects nurses' wellbeing, workforce sustainability, psychological safety and professional progression, creating implications for both patient outcomes and healthcare system functioning. Aim To articulate an evidence‐informed position that addressing structural racism in healthcare is a moral, ethical and professional responsibility of nurses, and to propose a conceptual framework positioning nurses as leaders of structural reform, governance accountability and equity‐driven healthcare transformation. Design Position paper drawing on interdisciplinary empirical evidence, ethical frameworks, workforce literature and contemporary nursing scholarship. Discussion This paper introduces the NSERF, which conceptualises structural racism as a multidimensional patient safety, workforce sustainability and governance accountability issue requiring coordinated nurse‐led structural advocacy and institutional reform. Structural racism is shown to operate through interconnected systems including healthcare policy, workforce structures, organisational governance, clinical practice and professional hierarchies, contributing to inequitable access to care, workforce exclusion, reduced psychological safety, burnout and poorer health outcomes. While nursing advocacy has historically focused on individual patient protection, this paper argues that structural advocacy is necessary to address systemic inequities embedded within institutional systems. Strategic reform directions include governance accountability, equity‐integrated clinical governance, workforce equity, structural competency education and policy engagement. Conclusion Structural racism compromises healthcare equity, patient safety, workforce sustainability and organisational trust. Nurses possess an ethical mandate, professional authority and practice‐informed insight to lead structural reform. Moving beyond interpersonal advocacy towards sustained structural advocacy is essential for developing equitable, culturally safe, accountable and sustainable healthcare systems.